Results of patient survival after surgical interventions for complicated forms of colon cancer performed in general surgical hospitals - M. A. Kubrak; S. M. Zavhorodnii; M. B. Danyliuk (Zaporozhye State Medical University, 2024)
The aim of the study: to evaluate the 1- and 3-year survival of patients operated for complicated forms of colon cancer (СC) in general surgical hospital. Materials and methods. The study group included 71 (100 %) patients with complicated forms of СС. Acute intestinal obstruction was detected in 49 (69.1 %) patients, tumor perforation - in 13 (18.3 %), acute colonic bleeding - in 3 (4.2 %) patients, a combination of acute intestinal obstruction with tumor perforation - in 4 (5.6 %) and intestinal obstruction with bleeding - in 2 (2.8 %) operated patients. Radical operations were performed in 48 (67.6 %) patients, palliative operations - in 18 (25.4 %), symptomatic operations - in 5 (7.0 %) patients. II stage of the disease was diagnosed in 15 (21.1 %), III stage - in 32 (45.1 %), IV stage - in 24 (33.8 %) operated patients. 19 (30.2 %) patients underwent specific chemotherapy after surgery. Results. Among patients with the II stage of the oncological process 1-year survival was 76.9 ± 11.7 %, 3-year - 53.8 ± 13.8 %; with stage III, 1-year survival was 65.6 ± 8.4 %, 3-year - 50.0 ± 8.8 %; in persons with IV stage of СC - 29.2 ± 9.3 % and 8.3 ± 2.6 % respectively (χ2 = 21.8, p = 0.0001). Among male patients, 1-year survival was 51.4 ± 8.5 %, 3-year - 31.4 ± 7.9 %; women - 61.1 ± 8.1 % and 44.4 ± 8.3 %, respectively (χ2 = 2.3, p = 0.1302). Better indicators were found in the case of cancer of the left sections of the large intestine than the right sections - the 1-year survival rate was 60.4 ± 7.1 % and 43.5 ± 10.3 % respectively; 3-year - 39.6 ± 7.1 % and 30.4 ± 9.6 % (χ2 = 0.74, p = 0.3906). Conclusions. The conducted analysis indicates a clear dependence of the survival results on the stage of the disease, gender and localization of the tumor process.